Table of Content - - (Journal of Humanities & Social Sciences, 2025)
Table of Content: 1. Soft Skills in Modern Education: A New Approach for Effective Educational Communication Dr. Mohamed Ouldhali 2. Design a model to measure the effect of interior spaces on individuals with hyperactivity and attention deficit disorder (ADHD) to develop them Ms. Nada Salem Al-Towairqi, Prof. Reem Farouq Al-Sabban 3. Mail in the Caliphate of Al-Walid bin Abdul-Malik (86-96 AH/705-715 AD) Mr. Khalid Abdullah Alsaeed 4. Spatial Analysis of Ambient Air Quality Variation in Dammam in Saudi Arabia Dr. Hessa Mohammed Aloatibi, Prof. Mohammed Ibrahim Al-Dagheiri 5. Globalization and Its Impact on the Consumption Pattern of Female University Students: An Applied Study on University of Hail Female Students Dr. Afaf Ali Al-Sayed, Lecturer Fathia Mohammed Al-Siddiq, Lecturer Lamia Saud Al-Aqili 6. The Use of Geographic Information Systems (GIS) in Measuring the Accessibility to Educational Services in the Driouch province: A Geographical Approach for Planning Dr. El-Kallouchi Mohamed, Dr. Ismail Bouguelba